A role for the Sts phosphatases in negatively regulating IFNγ‐mediated production of nitric oxide in monocytes. Issue 4 (25th August 2020) - Parashar, Kaustubh; Carpino, Nicholas
Abstract: Introduction: The atypical Sts phosphatases negatively regulate signaling pathways in diverse immune cell types, with two of their molecular targets being the related kinases Syk and Zap‐70. Mice lacking Sts expression ( Sts −/− ) are resistant to infection by the live vaccine strain (LVS) of Francisella tularensis . Although the mechanisms underlying the enhanced resistance of Sts −/− mice have not been definitively established, Sts −/− bone marrow‐derived monocytes (BMMs) demonstrate greater clearance of intracellular LVS following ex vivo infection, relative to wild type cells. To determine how the Sts proteins regulate monocyte bactericidal properties, we analyzed responses of infected cells. Methods: Monocyte bacterial clearance was assayed using ex vivo coculture infections followed by colony‐forming unit analysis of intracellular bacteria. Levels of gene expression were quantified by quantitative reverse‐transcription polymerase chain reaction, levels of Nos2 protein levels were quantified by Western blot analysis, and levels of nitric oxide (NO) were quantified directly using the Griess reagent. We characterized monocyte cytokine production via enzyme‐linked immunosorbent assay. Results: We demonstrate that Sts −/− monocyte cultures produce elevated levels of interferon‐γ (IFNγ) after infection, relative to wild type cultures. Sts −/− monocytes also demonstrate heightened responsiveness to IFNγ. Specifically, Sts −/− monocytes produce elevated levels of antimicrobial NO following IFNγ stimulation, and this NO plays an important role in LVS restriction. Additional IFNγ‐stimulated genes, including Ip10 and members of the Gbp gene family, also display heightened upregulation in Sts −/− cells. Both Sts‐1 and Sts‐2 contribute to the regulation of NO production, as evidenced by the responses of monocytes lacking each phosphatase individually. Finally, we demonstrate that the elevated production of IFNγ‐induced NO in Sts −/− monocytes is abrogated following chemical inhibition of Syk kinase. Conclusion: Our results indicate a novel role for the Sts enzymes in regulating monocyte antibacterial responses downstream of IFNγ. Abstract : Mice lacking Sts expression (Sts −/− ) are resistant to infection by the Gram‐negative bacterial pathogen Francisella tularensis live vaccine strain. Sts −/− monocytes display heightened responsiveness to interferon‐γ (IFNγ), by producing increased levels of nitric oxide and displayed enhanced upregulation of IFNγ‐responsive genes. These results indicate a novel role for the Sts enzymes in regulating IFG gamma signaling and monocyte antibacterial responses.